2021
DOI: 10.1186/s40594-020-00263-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective K-8 teachers’ noticing of student justifications and generalizations in the context of analyzing written artifacts and video-records

Abstract: Background This paper contributes to current discussions about supporting prospective teachers (PSTs) in developing skills of noticing students’ mathematical thinking. We draw attention to PSTs’ initial noticing skills (prior to instruction focused on supporting noticing) as PSTs engage in analyzing written artifacts of student work and video-records. We examined and compared PSTs’ noticing skills as they analyzed how students reason about, generalize, and justify generalizations of figural pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Based on the work written by SKR-01 and SKR-02, subjects with low mathematical generalization ability category have used only some phases of Mason's generalization. Students with low mathematical generalization ability only meet two phases: Perception of generalization and Expression of generalization (Magiera & Zambak, 2021;Setiawan et al, 2020).…”
Section: Students With Low Mathematical Generalization Ability (Skr)mentioning
confidence: 99%
“…Based on the work written by SKR-01 and SKR-02, subjects with low mathematical generalization ability category have used only some phases of Mason's generalization. Students with low mathematical generalization ability only meet two phases: Perception of generalization and Expression of generalization (Magiera & Zambak, 2021;Setiawan et al, 2020).…”
Section: Students With Low Mathematical Generalization Ability (Skr)mentioning
confidence: 99%
“…They identified that five preservice teachers teaching competence levels varied from not identifying any characteristics of students' understanding of pattern generalization to identifying different characteristics of students' understanding in detail. Also, Magiera and Zambak (2021) investigated preservice K-8 teachers' professional noticing of students' justifications and generalizations of figural patterns by using written artifacts and video-records. They found that preservice teachers provided more details about mathematically significant aspects of students' thinking when they analyzed students' written work compared to the video-records.…”
Section: In Terms Of Interpreting Important Mathematical Ideas In Students' Work In the Videosmentioning
confidence: 99%